2019
DOI: 10.1093/infdis/jiz380
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Evidence to Support a Correlate of Protection for Measles? A Systematic Review

Abstract: Background Many studies assume that the serologic correlate of protection from measles disease is 120 mIU/mL. We systematically reviewed the literature to examine the evidence supporting this correlate of protection. Methods We searched peer-reviewed and gray literature for articles reporting a measles correlate of protection. We excluded studies focusing on special populations, infants aged <9 months, and those using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…However, potential confounders, such as differences in exposure risk over time, must be considered carefully in this type of analysis. Any measured level or correlate of protection will be specific to the assay used in the studies, as was the case for measles (22). Even for measles, where a correlate of protection has been used consistently, a recent review found little evidence to support the threshold used, suggesting this threshold needs refinement (22).…”
Section: Analytical Methods To Infer Correlates Of Protectionmentioning
confidence: 99%
“…However, potential confounders, such as differences in exposure risk over time, must be considered carefully in this type of analysis. Any measured level or correlate of protection will be specific to the assay used in the studies, as was the case for measles (22). Even for measles, where a correlate of protection has been used consistently, a recent review found little evidence to support the threshold used, suggesting this threshold needs refinement (22).…”
Section: Analytical Methods To Infer Correlates Of Protectionmentioning
confidence: 99%
“…because pre-outbreak serum samples were available for investigation (examples in [25][26][27]). Such samples may be available when surveillance is being performed for increased risk of infections in occupational settings, such as in a health-care setting, refugee workers or for the military service.…”
Section: Article Highlightsmentioning
confidence: 99%
“…Nach überstandener Krankheit besteht lebenslange Immunität. Ein Masern-Serum-Titer von 120-300 mIU/mL gilt bei Experten häufig als Korrelat für Protektion vor Masern [3].…”
Section: Update 2020unclassified